Filtry piaskowe w ochronie roślin przed chorobami w szkółkach - Kubiak, Katarzyna; Oszako, Tomasz (Leśne Prace Badawcze, 2010)
In some nurseries to irrigate plants water must be taken from natural reservoirs. Rivers and lakes are often polluted with microorganisms and a proportion of these are pathogenic to cultivated forest tree species. To avoid the infection of seedlings due to plant irrigation with contaminated water, a system of Slow Sand Filters (SSF) was designed and installed in the Kiejsze forest nursery (Koło Forest District in central Poland). Tests of slow sand filters efficiency were performed using qPCR to assess their effectiveness in reducing the concentration of bacterial DNA in filtrated water. Measurements after filtration through SSF, revealed a significant reduction in bacterial DNA. After 24 hours, 60% of Rhizobium tumefaciens was eliminated and that progressed to 71% after 48 h. In the case of Pseudomonas syringae , purification of water was even more efficient, 67% after 24 h and 74% after 48 h, and there was a similar reduction for Xanthmonas campestris (71% and 70%, respectively). These data allow us to recommend this approach to water purification as an alternative preventive method for plant protection in nurseries.